Analysis of the mental health of people with diabetes during the period of the COVID-19 pandemic in Brazil: A systematic literature review (Research, Society and Development, 2023)
The concern with the population's mental health (MH) has worsened during the serious social crisis involved in the process of spreading the SARS-CoV-2 virus, mainly in view of the unpredictability of the time of the pandemic and its consequences. Phenomena like this usually generate psychological and social disturbances, which impact on the coping capacity of an entire society. Assessing the increase in psychopathological comorbidities over the course of the pandemic period, this systematic literature review aims to analyze the MH of people with Diabetes Mellitus (DM) during the COVID-19 pandemic in Brazil. For this, a systematic review of the literature was carried out, of a qualitative and exploratory nature, through searches in SciELO and the Virtual Health Library (VHL), in which the time period from 2020 to 2022 was established. 44 articles were found, after the eligibility criteria, 8 works were selected. According to the data presented, the MH of DM patients, who already had an elevated risk of depression, aggravated due to stress (37.7%), anxiety (43.3%) and depression (45.1%), mainly during the period of social distancing, reflecting on the worsening quality of life of individuals with DM during this period. Thus, the impact generated by the pandemic regarding the MH of people living with DM and other comorbidities is evident, making it necessary to adopt a humanized approach through the creation of resources and lines of care aimed at this demand, with the aim of building of inclusive public policies, contemplating the emotional and social aspects of the population.